Melons: Safe Handling Practices for Consumers - Amy Simonne (EDIS, 2002)
This publication is FCS8744, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Adapted from the FDA Manual Retail Food Safety Produce Safety at Retail: Safe Handling Practices for Melons. Publication date: November 2002.